2018
DOI: 10.29333/ejmste/81811
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Students’ Conceptions of Learning Science by Augmented Reality and their Scientific Epistemic Beliefs

Abstract: Previous studies have addressed the positive influences of augmented reality (AR) on science learning. However, few studies have explored how learners consider learning science by such an emerging technology, particularly from the perspectives of conceptions of learning. This study therefore aimed to develop a survey to understand students' conceptions of learning science by AR (CLSAR) considering their demographic characteristics and scientific epistemic beliefs. The CLSAR survey was validated by the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
21
0
7
Order By: Relevance
“…The recent CLSAR survey results have shown that the students have shown positive conceptions, with stronger perceptions of learning science by AR as increasing motivation and interaction (Cheng, 2018).…”
Section: Development Of the Educational Environment For Learning Objementioning
confidence: 99%
“…The recent CLSAR survey results have shown that the students have shown positive conceptions, with stronger perceptions of learning science by AR as increasing motivation and interaction (Cheng, 2018).…”
Section: Development Of the Educational Environment For Learning Objementioning
confidence: 99%
“…Spatial ability, defined as the ability to visualize an object geometry from different angles, rotation and integration or integration of parts of a given object [8][9][10] [11], can be improved and investigated further through 3DMetric media based on Augmented Reality (AR) technology [12]. AR media is an integration of digital elements that are added to the real-world in real-world (real-world data) and follow real-world environments and can be applied to mobile devices [13][14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of technology has transformed the learning environment into a more engaging, interactive, authentic, and joyful environment (Cheng, 2018;Gan & Balakrishnan, 2018). Various technologies such as multimedia, internet, mobile devices, Internet of Things (IoT), virtual reality, and AR are integrated into the education system (Kiryakova, Angelova, & Yordanova, 2018).…”
Section: Introductionmentioning
confidence: 99%